IMPLEMENTATION OF BALI GOVERNOR REGULATION NUMBER 97/2019 THROUGH A POSTMODERN APPROACH STUDY - Sri Lestari; I Wayan Ardika; I Nyoman Wijaya (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2020)
This study talks about the meaning of journalists, intellectuals and cultural observers of the Koster Ace government Governor Regulation No. 97 of 2018 which began to be implemented at the end of 2018.This policy aims to serve as a guideline by the local government of Bali in formulating technical policies in the field of limiting plastic waste generation Disposable (PSP). This phenomenon is studied using a Postmodern approach, so that the methodology, theory, epistemology, and research objectives must be in sync with it. The methodology is taken from a genealogy method which is in sync with Foucault's theory of power relations of knowledge. Assisted by Bourdieu's generative structural theory. The goal is to get an understanding or meaning of the meaning of the regulation. Meaning in studies comes from 'from within' through the point of view of the actors who practice the meaning itself. Every form of meaningful practice is influenced by épistémè, reasoning, and experiences that shape the knowledge of its meaning as conceptualized in Foucault's theory and Bourdieu's cultural capital. Substantially, all interpreters agree that this regulation is one way to overcome the problem of single-use plastic waste (PSP), but there are still many weaknesses when it is implemented in the community. The weakness lies in the absence of an in-depth academic study before the regulation is implemented. As the essence of the conclusion, it can be seen that the meaning of journalists, intellectuals, and humanists for the governorship shows a contestation (struggle or resistance), but in it there is no visible negotiation of the dominant powers. Their meaning can be referred to as a form or reflection of the level of knowledge of each interpreter, which ultimately leads to productive powers towards Pergub No. 97 of 2018. Keywords: meaning, journalist, intellectual, humanist, governorate